Impact of Divalent Metal Additives on the Structural and Optoelectronic Properties of CH3NH3PbI3 Perovskite Prepared by the Two-Step Solution Process. (16th January 2017) - Watthage, Suneth C.; Song, Zhaoning; Shrestha, Niraj; Phillips, Adam B.; Liyanage, Geethika K.; Roland, Paul J.; Ellingson, Randy J.; Heben, Michael J.
ABSTRACT: Here, we investigate the effect of divalent metal (Zn 2+, Cd 2+ and Hg 2+ ) on the structural and optoelectronic properties of methylammonium lead iodide perovskite materials prepared by the two-step deposition process. The incorporation of Cd 2+ significantly improved the grain size, crystallinity, and charge carrier lifetime of CH3 NH3 PbI3 . The inclusion of Hg 2+ and Zn 2+ improved the grain size compare to the control sample but adversely affected the optoelectronic properties of perovskite films. The Hg- and Zn-based impurities were formed on the surface of the films, which increased the charge trap density and lead to high non-radiative recombination rate. Time resolved photoluminescence measurements indicated that the Cd and Zn point defects do not create deep-level trap states, but the Zn-modified film showed a low lifetime due to morphology changes in the film and particle segregation on the surface.